Pengaruh Kepuasan Kerja Terhadap Produktivitas Karyawan Pada Usaha Konveksi dan Percetakan Mattoangin di Kota Makassar - safrin safrin; Sulaiman sulaiman (Economy Deposit Journal (E-DJ), 2020)
Based on the results of observations that there has been a decrease in employee job satisfaction at the Mattoangin convection and printing business in the city of Makassar, which has an impact on work productivity. There are several factors that cause this, including a lack of employee work efficiency and a lack of rewards for employees who excel. Employees expect rewards for their performance, achievements because the majority of jobs are related to the safety of their body and soul. This dissatisfaction attitude is implemented in attitude, loyalty, level of discipline, and work productivity. This research was conducted with the aim of knowing the effect of job satisfaction on employee productivity at the Mattoangin printing and convection business in the city of Makassar. The type of data used is primary data obtained by distributing questionnaires. The number of samples in this study was 30 employees at the Mattoangin convection and printing business, where the sampling was done using saturated techniques. The questionnaire obtained was tested for validity, reliability, and normality test. The data analysis method used is a simple regression analysis. The results showed that job satisfaction had a positive and significant effect on employee work productivity at the Mattoangin convection and printing business in Makassar city. This means that work itself, relationships with superiors, relationships with colleagues, promotions, and salaries/wages are closely related to work productivity. If other variables are constant, the Y value will change by 0.803 per unit X.Keywords: Job satisfaction, productivity and employee